Artepillin C as an outstanding phenolic compound of Brazilian green propolis for disease treatment: A review on pharmacological aspects - Beserra, Fernando Pereira [UNESP]; Gushiken, Lucas Fernando Sérgio [UNESP]; Hussni, Maria Fernanda [UNESP]; Ribeiro, Victor Pena; Bonamin, Flávia; Jackson, Christopher John; Pellizzon, Cláudia Helena [UNESP]; Bastos, Jairo Kenupp (Wiley, 2020)
Propolis is a viscous resin consisting of plant material (shoots, flowers, and plant exudates), salivary secretions and waxes produced by Apis mellifera bees. Its popular use aroused the interests of scientific research, which proved to be a potential source of various bioactive substances. The chemical composition of propolis depends on several factors, such as the different types of plant sources collected by bees, geographic origin, and the time of year in which they are produced, but it is known that phenolic represent the main bioactive constituents of propolis. Baccharis dracunculifolia DC (Asteraceae) is the most important botanical source of propolis and a native to southeastern Brazil. It is widely known as the green propolis because of its deep green color. One of its major phenolic acids is artepillin C (Art-C), a diprenyl-p-hydroxycinnamic acid derivative. This review aims to provide a comprehensive summary of the pharmacological effects of Art-C. The limited number of publications on this topic over the past two decades have been collected from databases and summarized. Numerous biological activities have been described for the Art-C, such as gastroprotective, anti-inflammatory, antimicrobial, antioxidant, antitumor. This article describes aspects of occurrence, synthesis, biological activities and pharmacokinetic approaches.
Keywords: artepillin C; green propolis; pharmacological properties; phenolic compounds